Variation in Expression of the HECT E3 Ligase UPL3 Modulates LEC2 Levels, Seed Size, and Crop Yields in Brassica napus. Issue 10 (22nd August 2019) - Miller, Charlotte; Wells, Rachel; McKenzie, Neil; Trick, Martin; Ball, Joshua; Fatihi, Abdelhak; Dubreucq, Bertrand; Chardot, Thierry; Lepiniec, Loic; Bevan, Michael W.
Abstract : Variation in the expression of UPL3 modulates LEC2 levels, seed size and crop yield in Brassica napus . Abstract: Identifying genetic variation that increases crop yields is a primary objective in plant breeding. We used association analyses of oilseed rape/canola ( Brassica napus ) accessions to identify genetic variation that influences seed size, lipid content, and final crop yield. Variation in the promoter region of the HECT E3 ligase gene BnaUPL3 . C03 made a major contribution to variation in seed weight per pod, with accessions exhibiting high seed weight per pod having lower levels of BnaUPL3 . C03 expression. We defined a mechanism in which UPL3 mediated the proteasomal degradation of LEC2, a master transcriptional regulator of seed maturation. Accessions with reduced UPL3 expression had increased LEC2 protein levels, larger seeds, and prolonged expression of lipid biosynthetic genes during seed maturation. Natural variation in BnaUPL3 . C03 expression appears not to have been exploited in current B . napus breeding lines and could therefore be used as a new approach to maximize future yields in this important oil crop.